Various Forms of Chineseness in the Origins of Southeast Asian Communism - Kankan Xie (Left Transnationalism: The Communist International and the National, Colonial, and Racial Questions, 2020)
People often see the origins of communist movements in Southeast Asia and the region’s overseas Chinese community as closely intertwined. This perception is evident in the cases of densely Chinesepopulated areas such as Malaya and Siam (Thailand), as well as places like Vietnam and Cambodia, where China’s influence has been historically strong in both political and cultural domains. Admittedly, it is very convenient to connect many Chinese-involved communist activities in Southeast Asia to the emergence of the communist party in China, but the simplistic argument – that Southeast Asia imports communism from China – is severely problematic. While overseas Chinese...